A novel long-term intravenous combined with local treatment with human amnion-derived mesenchymal stem cells for a multidisciplinary rescued uremic calciphylaxis patient and the underlying mechanism. (10th February 2022) - Qin, Lianju; Zhang, Jing; Xiao, Yujie; Liu, Kang; Cui, Yugui; Xu, Fangyan; Ren, Wenkai; Yuan, Yanggang; Jiang, Chunyan; Ning, Song; Ye, Xiaoxue; Zeng, Ming; et al.
Abstract: Calciphylaxis is a rare disease characterized histologically by microvessel calcification and microthrombosis, with high mortality and no proven therapy. Here, we reported a severe uremic calciphylaxis patient with progressive skin ischemia, large areas of painful malodorous ulcers, and mummified legs. Because of the worsening symptoms and signs refractory to conventional therapies, treatment with human amnion-derived mesenchymal stem cells (hAMSCs) was approved. Preclinical release inspections of hAMSCs, efficacy, and safety assessment, including cytokine secretory ability, immunocompetence, tumorigenicity, and genetics analysis in vitro, were introduced. We further performed acute and long-term hAMSC toxicity evaluations in C57BL/6 mice and rats, abnormal immune response tests in C57BL/6 mice, and tumorigenicity tests in neonatal Balbc-nu nude mice. After the preclinical research, the patient was treated with hAMSCs by intravenous and local intramuscular injection and external supernatant application to the ulcers. When followed up to 15 months, the blood-based markers of bone and mineral metabolism improved, with skin soft tissue regeneration and a more favorable profile of peripheral blood mononuclear cells. Skin biopsy after 1-month treatment showed vascular regeneration with mature noncalcified vessels within the dermis, and 20 months later, the re-epithelialization restored the integrity of the damaged site. No infusion or local treatment-related adverse events occurred. Thus, this novel long-term intravenous combined with local treatment with hAMSCs warrants further investigation as a potential regenerative treatment for uremic calciphylaxis due to effects of inhibiting vascular calcification, stimulating angiogenesis and myogenesis, anti-inflammatory and immune modulation, multidifferentiation, re-epithelialization, and restoration of integrity.